In vitro EVALUATION OF ANTIDIABETIC, ANTIOXIDANT AND PROBIOTIC ATTRIBUTES OF Lactobacillus casei strain NCDC 357 (Applied Biological Research, 2023)
The present study was aimed to evaluate the antidiabetic and antioxidant  activities of a lactic acid bacterial strain ‘Lactobacillus casei NCDC 357’,  and to investigate its probiotic characteristics. The antidiabetic activity was examined by evaluating the α-glucosidase and α-amylase inhibitory  activities. L. casei strain NCDC 357 exhibited antidiabetic activities by α glucosidase (67.7% and IC50 38.08 μL) and α-amylase (53.6% and IC50 49.96 μL). The strain showed antioxidant activities by DPPH (53.4% and  IC50 77.60 μL) and ABTS (48.7% and IC50 51.48 μL). Further, the strain  was resistant to simulated gastrointestinal juice and showed potential for  health promotiobased on adhesion, antibiotic susceptibility, and anti microbial activities. L. casei NCDC 357 appeared to be a potential  probiotic having beneficial health effects.
Keywords: Antidiabetic activity; antioxidant activity; Lactobacillus casei; probiotic; strain evaluation